SKRINING PENYAKIT DIABETES MELLITUS DI DESA PEMECUTAN KAJA DENPASAR UTARA - Ni Putu Eka Febianingsih; NLP Suardini Yudhawati; Kmg Agus Jerry Widyanata; I Wayan Wardita; I Ketut Dira (Jurnal Pengabdian kepada Masyarakat Wahana Usada, 2019)
New cases of Diabetes Mellitus (DM) in Bali Province from 2011 to 2013 were increased. Based on the report of Integrated Disease Surveillance or Surveilan Terpadu Penyakit (STP) from Puskesmas it is known that DM was ranked 3 out of the 10 highest diseases in health centers throughout the City of Denpasar. The purpose of this screening is to find out the prevalence of DM in Pemecutan Kaja Village, North Denpasar in 2015. Methods: Screening was carried out on 189 subjects aged ?15 in Pemecutan Kaja Village, North Denpasar on January 6 and 7, 2015. Screening was carried out by checking blood sugar levels while using Nesco Multicheck. The collected data is processed and presented descriptively about thecharacteristics of the sample and the proportion of DM based on the results of the examination. Results: The results showed that 6.4% of respondents suffering DM. Most of the subjects were women (58.3%). In this screening, there are 50% in the age group ?51 years, and most are only elementary school graduates (30%). Based on the type of work, most of the subjects are entrepreneurs/traders (50%). Based on the interview, there was none history of DM in the family. Conclusion: The proportion of DM in Pemecutan Kaja Village is 6.4% through examination of blood sugar levels while using Nesco Multi Check. The positive results of DM in this screening should be carried out further examination to confirm the diagnosis so that appropriate treatment can be carried out.